Competition, concentration and efficiency of commercial banks in South Korea, mainland China and Taiwan - Huang,Juan (Enrich series on China's economic issues, 2012)
This book studies the development of commercial banks in Mainland China, Taiwan and Korea. Based on empirical data, the author comes to the conclusion that the nature of the banking sector is monopolistic and that competition and consolidation can co-exist. The data also shows that competition and the number of banks operated are not necessarily related and that under normal circumstances competition can improve the efficiency of banks.